Colonization of the Argentinean Mesopotamia by Chaco Chachalaca (Ortalis canicollis) - Fraga, Rosendo Manuel (2021)
We report information from museum specimens, online databases, bibliographic records and field data that show colonization of the Argentinean provinces of Entre Ríos and Corrientes (Argentinean Mesopotamia) by Chaco Chachalacas (Ortalis canicollis). This colonization probably started during the first decades of the 20th Century, and this cracid is currently expanding its range towards the Uruguay River basin.